Effects of fire on CO2, CH4, and N2O exchange in a well‐drained Arctic heath ecosystem - Hermesdorf, Lena; Elberling, Bo; D'Imperio, Ludovica; Xu, Wenyi; Lambæk, Anders; Ambus, Per L. (Global change biology, 2022)
Wildfire frequency and expanse in the Arctic have increased in recent years and are projected to increase further with changes in climatic conditions due to warmer and drier summers. Yet, there is a lack of knowledge about the impacts such events may have on the net greenhouse gas (GHG) balances in Arctic ecosystems. We investigated in situ effects of an experimental fire in 2017 on carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) surface fluxes in the most abundant tundra ecosystem in West Greenland in ambient and warmer conditions. Measurements from the growing seasons 2017 to 2019 showed that burnt areas became significant net CO2 sources for the entire study period, driven by increased ecosystem respiration (ER) immediately after the fire and decreased gross ecosystem production (GEP). Warming by open‐top chambers significantly increased both ER and GEP in control, but not in burnt plots. In contrast to CO2, measurements suggest that the overall sink capacity of atmospheric CH4, as well as net N2O emissions, were not affected by fire in the short term, but only immediately after the fire. The minor effects on CH4 and N2O, which was surprising given the significantly higher nitrate availability observed in burnt plots. However, the minor effects are aligned with the lack of significant effects of fire on soil moisture and soil temperature. Net uptake and emissions of all three GHG from burnt soils were less temperature‐sensitive than in the undisturbed control plots. Overall, this study highlights that wildfires in a typical tundra ecosystem in Greenland may not lead to markedly increased net GHG emissions other than CO2. Additional investigations are needed to assess the consequences of more severe fires. We investigated the effects of an experimental fire on carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) surface fluxes in an Arctic upland ecosystem with and without summer warming. Overall, this study highlights that wildfires in a typical tundra ecosystem in Greenland may not lead to markedly increased net GHG emissions other than CO2.